Peningkatan Produksi Padi Melalui Penguatan Kelembagaan Perbenihan Padi Di Nagari Lubuk Pandan, Kecamatan 2 X 11 Enam Lingkung - Ivonne Ayesha (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2018)
This study aims to identify the institutions that play a role in the procurement of rice seeds, describe the role of each institution, and develop policy recommendations for institutional strengthening of rice seed. The research was conducted in Nagari Lubuk Pandan, District 2x11 Six Lingkung, Padang Pariaman District, West Sumatera Province. The respondents' farmers were deliberately determined by 35 people based on the guidance of Wali Nagari and community leaders. Data were analyzed descriptively and presented in table and diagram. The results showed that 1) Institutional of rice seed in Nagari Lubuk Pandan consist of formal and informal institution. The formal institutions are Gapoktan